Biomass resources and thermal conversion biomass to biofuel for cleaner energy: A review - Thi Bich Ngoc Nguyen; Nguyen Viet Linh Le (BIORE Scientia Academy, 2023)
Biofuel is considered as one of the solutions to future energy problems. Unlike fossil fuels, biofuel is a renewable fuel source produced from biomass. Biomass comes from a wide variety of plants and animals and even waste. Therefore, the production of biofuel from biomass is promising not only to solve energy problems but also to solve other social problems. This study will present some of the most potential biomass sources and thermal conversion processes of biomass for biofuel production.